Profile of the Dysphagic Patient treated at the dysphagia outpatient clinic of the Onofre Lopes University Hospital - Conrado, Nícolas; Otto Gomes, Eduardo; Maria de Brito Macedo Ferreira, Lidiane; De Paula Bedaque, Henrique; Alexandre Silva, Camila; Barbosa de Lima, Mateus (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
Objective: Oropharyngeal dysphagia is a clinical condition with high prevalence and impact on the quality of life of the population, therefore, the present study aimed to elaborate the profile of this patient treated at the outpatient clinic of the Hospital Universitário Onofre Lopes. Methodology: The study evaluated fifty-nine patients through anamnesis and application of the Dysphagia Handicap Index (DHI), associated with video swallowing endoscopy (VED) in order to determine the degree of dysphagia in these individuals and classify them according to the criteria de Macedo e Filho, Yale scale for the presence of food residues, Souza parameter for posterior oral leakage and FOIS scale. Results: It was found that choking, coughing and choking were the signs and symptoms most present in the subjects. Posterior oral leakage, presence of residues in valleculae and pyriform recesses were the most frequent findings in VED. Most patients obtained FOIS classification 5, followed by FOIS 7. Furthermore, a correlation was observed between the total DHI value and the FOIS classification, so that the former is capable of predicting this in 16%. Finally, a difference was found in the total DHI averages for mild and severe dysphagia. Conclusion: For the studied population, we identified choking as the most frequent symptom, posterior oral leakage as the most observed VED finding and DHI prediction for FOIS in 16%.